Pembentukan Keluarga Sakinah dan Problematikanya pada Keluarga Muslim di Kota Banjarmasin dalam Perspektif Sosiologi Hukum Islam - Ibrahim, Malik (Universitas Proklamasi 45, 2022)
The family is the smallest form of society, the good and bad of society are strongly influenced by the good and bad of a family. Therefore, fostering and empowering the family becomes a necessity. And the more modern human life is, the more complex the problems faced will be considering the increasingly complex problems faced by mankind. The effort to create a sakinah family is no exception. For this reason, this study seeks to map the problems in realizing a sakinah family, especially in the Banjarmasin City area, South Kalimantan.This article highlights two things, first, efforts to establish a sakinah family and its problems in Muslim families in Banjarmasin City. Second, efforts to establish and overcome the problems of the sakinah family in Muslim families in Banjarmasin City in the perspective of Sociology of Islamic Law. The Sociological Approach of Islamic Law was chosen for analyzing this research because not achieving a sakinah family cannot be separated from social aspects, both in the family realm and in the wider community.